Civil law & litigation for paralegals - Bevans, Neal R. (McGraw-Hill, 2008)
Civil Law & Litigation for Paralegals provides the student with an in-depth analysis of the wide variety of civil cases, laying out the basic foundation of the American legal system, proceeding through the investigation and implementation of a civil case, and following the case through to appeal. It not only teaches the basics of civil litigation, but also gives students the chance to build a skill set and create material for a portfolio that can be used for prospective employers.